Multifunction table lamp / Nurul Hanis Syafiqah Mohd Ripin - Mohd Ripin, Nurul Hanis Syafiqah (2021)
MUJI develop enjoyable and low-cost items by optimising the manufacturing process. MUJI has been creating no-frills quality products based on the three concepts of "material selection," "process streamlining," and "packaging simplicity." They have been promoting a consistent philosophy in every aspect such as product development, store environment and customer service. They attempt to create a welcoming environment for customers to purchase in. In this case study analysis, it is focusing on the furniture, interior and home appliances produced by MUJI production to be analyses, investigate, and identify along with their current issues and point out the solutions that can be used in the MUJI company to improve the existing product. Therefore, some analysis and implementations have been done. moreover, SWOT analysis also been point out to enhance its strength and find initiatives to improve company’s weakness.